Reconfigurable Intelligent Surface-Assisted Bluetooth Low Energy Link in Metal Enclosure - Lodro, Mir; Gradoni, Gabriele; Gros, Jean-Baptiste; Greedy, Steve; Lerosey, Geoffroy (Frontiers in Communications and Networks, 2021)
Reconfigurable intelligent surface (RIS) technology is at the forefront for its transformative role in future wireless communication systems such as wireless local area networks (WLAN), sixth-generation (6G) communication, and internet-of-things (IoT). This paper presents RIS-assisted Bluetooth low energy (BLE) communication links in neighbor discovery mode. We optimized the packet error rate (PER) performance of the BLE communication link in a highly reflecting metal enclosure environment. We used one RIS for the PER optimization of four BLE physical (PHY) modes. Then, we used two RISs simultaneously in a distributed and centralized manner to further optimize the PER of all BLE PHY modes. We found PER optimization using two RISs is better than the PER optimization using one RIS. Additionally, PER optimization using a centralized arrangement of RISs outperformed PER optimization using distributed arrangement. We found the coded BLE modes i.e. LE500K and LE125K show lower PER than the uncoded counterpart i.e. LE1M and LE2M. This is because uncoded BLE PHY modes have higher data rates than the coded BLE PHY modes. Because of additional channel power gains introduced by RIS-based passive beamforming, the PER of coded and uncoded BLE PHY modes is further reduced.